Maternal nutrition and offspring lung health: sex-specific pathway modulation in fibrosis, metabolism, and immunity - Shuangyi Zhao; Zhimin Chen; Huina Liu; Xinyan Wang; Xiuru Zhang; Huirong Shi (Food & Nutrition Research)
Background: Maternal nutrition profoundly influences offspring health, impacting both prenatal and early postnatal development. Previous studies have demonstrated that maternal dietary habits can affect key developmental pathways in the offsprings, including those related to lung function and disease susceptibility. However, the sex-specific impact of a maternal high-salt diet (HSD) on offspring lung injury remains poorly understood. Objective: This study aimed to investigate the sex-specific effects of maternal HSD on lung injury in mouse offsprings, focusing on pathways related to fibrosis, metabolism, immunity, and apoptosis. Design: Pregnant C57BL/6J mice were subjected to either normal or HSD conditions during gestation. Lung tissues from the male and female offsprings were analyzed using high-throughput RNA sequencing and bioinformatics tools to examine transcriptomic changes. Wet-lab validation, including Masson trichrome staining, immunofluorescence for α-SMA, and qRT-PCR for fibrotic markers (α-SMA, collagen I, Fn1, and TGF-β), was conducted to confirm fibrosis and other injury markers. Lung structure and weight were also evaluated to assess physical alterations due to maternal diet. Results: Maternal HSD significantly altered lung transcriptomes in a sex-specific manner. Male offsprings showed increased susceptibility to fibrosis, as confirmed by histological and molecular analyses, including elevated expression of α-SMA, collagen I, Fn1, and TGF-β. In contrast, female offsprings exhibited distinct changes in metabolic and immune pathways. These findings highlight the differential regulation of pulmonary injury mechanisms between male and female offsprings exposed to HSD. Conclusions: Maternal HSD induces sex-specific lung injury in offsprings by disrupting critical pathways involved in fibrosis, metabolism, immunity, and apoptosis. The combination of transcriptomic and orthogonal data underscores the need for balanced maternal nutrition during pregnancy to promote long-term respiratory health in offsprings. These results provide new insights into the sex-specific vulnerabilities to lung disease arising from maternal diet.